Não morda a língua portuguesa : norma culta ou norma curta? - Melo, Ricardo Celso Ulisses de (2015)
Despite the theoretical and practical ramifications arising from sociolinguistic studies in Brazil, the 90s brought the resurgence of a set of reflections on language which, expressed in newspaper columns, school grammars, books “no more mistakes" and writing manuals of major newspapers and public administration bodies, spreads the belief that there is only a "right" way to use language and that is the only acceptable way: the standard norm. All others are "wrong", and should be avoided. In this line of thought, in the state of Sergipe stands the book "Do not bite the Portuguese language", authored by Professor Wilma Ramos, described in its 10th edition as a reference guide for everyday difficulties of the Portuguese language, which brings advice on how to use the language in the light of the grammar of standard variant.This research aims to analyze prescriptions contained in the book “Do not bite the Portuguese language”, which disregard lessons contained in the normative instruments reference of Portuguese and disqualify the several varieties non-standard, as its speakers;discuss lessons that reject typical linguistic phenomena of Brazilian Portuguese, not welcomed by normative instruments reference of the Portuguese language, but widely disseminated in speech or writing from educated urban speakers, and, moreover, to assert the principles underlying the work “Do not bite the Portuguese language”, its contribution to the process of social representation of language and its implications for the process of teaching and learning Portuguese.The theoretical framework will focus in the postulates of sociolinguistics, whose studies have evidenced that natural languages are characterized by the phenomenon of variation and change and that the cultured varieties coexist with the informal varieties in a complex process of interactions, making room for the recognition of the legitimacy of difference, which are a result of the recent publication of the first grammars aimed for variety of Portuguese spoken in Brazil. Based on the norm concept in Coseriu, they seek to clarify the use of the terms "cultured norms", "standard norm", "grammatical norm", "pedagogical norm", "popular norm", characterizing Brazilian linguistic reality as essentially tripartite, formed by a standard norm, a set of prestigious norms and a large range of popular standards. It will set-up the concept of short standard, based on Faraco, to show their materialization in the work under review. It will also discuss the concept of legitimate language, as Bourdieu, aiming to outline the large-scale social factors involved in the construction processof the standard norm,in order to correlate linguistic issues properly with its institutional interface.The process of building the legitimate language, coupled with the sociolinguistic conception of the variation phenomenon, will provide the basis to place the institutional role of the work from Professor Wilma Ramos and discuss their implications for the Portuguese language teaching-learning process. The reference normative instruments of Portuguese language were chosen from grammars and dictionaries in vogue in the second half of the twentieth century, whose authors are or were consecrated philologists. Regarding the dictionaries, works ratified by the National Textbook Program will also be used – Dictionaries.